(untitled) (Journal of Social Sciences Review, 2025)
This research paper examines the contributing factor to sustainable consumption behavior by considering the role of Sustainable Behavior Intention (SBI), as the mediator, and Social Pressure (SP) as the moderator. Through a structured questionnaire and 303 respondents, the study looks at the implications of PCE, EC, and HC on SBI and SCB. Performance, analysis shows that both PCE and EC have positive effects on SBI, and SCB lending credence to the need to enhance consumer belief in efficacy and responsibility for nature. The analysis of the relationship between HC and SCB or SBI demonstrates that, while SCB is a priority for HC, impacting on SBI is statistically not significant focusing on health benefits in place of environmental intentions. Intention is identified as the key link between PCE and EC, with SCB being an intermediary mediated by SBI. Nevertheless, SP fails to moderate the SBI-SCB relationship to denote a shift in intrinsic motive related to sustainability decision-making. The results reported in this paper are relevant to business managers and policymakers. Special emphasis should be placed on educational activities that would develop people’s perceptions of the environment as a valuable resource and encourage people to make their decisions independently.